Against - Madeleine P. Kendall; Fabricio da Silva Costa; Yinka Oyelese; Daniel L. Rolnik (Clinical Obstetrics & Gynecology, 2026)
Pre-eclampsia is a pregnancy disorder associated with substantial maternal and perinatal morbidity and mortality worldwide. Low-dose aspirin initiated during the first trimester can reduce the risk of preterm pre-eclampsia, leading some to advocate universal prophylaxis during pregnancy. Although simple in principle, this approach would unnecessarily expose many low-risk women to treatment while providing limited absolute benefit. Moreover, the effectiveness of aspirin depends on treatment adherence, which may be reduced without individualized risk assessment. Current evidence supports targeted aspirin prophylaxis following first-trimester risk stratification rather than universal treatment, an approach that has not been evaluated in adequately powered randomized trials.